Evaluasi Supply Chain Management pada Pelayanan Fasilitas Keselamatan dan Kesehatan Kerja (K3) terhadap Temuan Kondisi dan Tindakan Tidak Aman (KTA TTA) pada Klinik Perusahaan Tambang X Kabupaten Karimun Provinsi Kepulauan Riau - Winahyu, Arizky; Paramarta, Vip (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research aims to evaluate logistics management or Supply Chain Management at the Occupational Safety and Health (K3) Facility of the X Mining Company Clinic which operates in Karimun Regency, Riau Islands Province, especially the types of medicines and first aid equipment which have a correlation with the potential for implementing first aid in injuries based on findings of Unsafe Actions (TTA) and Unsafe Conditions (KTA). This research is descriptive-evaluative research which broadly describes, records, analyzes and interprets the actual conditions occurring in the field with the standards of needs that should be met. The population in this study were all employees of Mining Company . The research results show that the logistics management of medicines and first aid equipment at the X Mining Company Clinic has not fully considered the potential for implementing first aid for injuries based on findings of Unsafe Actions (TTA) and Unsafe Conditions (KTA). It is hoped that there will be improvements in planning for the procurement of medicines and first aid equipment so that they are more in line with the operational conditions of Mining Company X.